FORMULATION AND EVALUATION OF FLOATING IN SITU GEL OF OMEPRAZOLE MAGNESIUM FOR ORAL DRUG DELIVERY SYSTEM - SONI, ANKIT; MAHESH KUMAR KATARIA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Omeprazole magnesium is indicated for the treatment of erosive esophagitis associated with gastroesophageal reflux disease. It is one of the highly prescribed proton pump inhibitor in the management of peptic ulcer diseases. The therapeutic concentration of a drug in blood can be maintained for a prolonged period of time by administering it in the form of in situ floating gel dosage form. Omeprazole magnesium undergoes degradation at a low pH of the esophagus and stomach; it is therefore given as in situ gel, so, there is minimum contact with acidic pH. Methods: Omeprazole magnesium suspension prepared using various polymers and floating agents in varying concentrations. Several evaluation tests including dissolution test to ensure the release of the drug from formulation by in vitro technique, color and homogeneity, in vitro floating duration, in vitro gelling capacity, drug content determination, pH of the formulation, and floating lag time were studied. Results: All formulations demonstrated good Fourier-transform infrared compliance and no interaction between drug, polymer, and other excipients. The study’s findings show that the formulation F6 showed the best results. Conclusion: The developed formulation was a viable alternative conventional solution by virtue of its ability to enhance bioavailability through its longer gastric residence time and ability to sustain drug release as well as the advantage of floating and pH which minimize the degradation of omeprazole magnesium which is easily degraded by acidic environment.